Person-centred care for dementia patients (back-end system development) - Sahidha Nasreen Syed Abu Backer (Nanyang Technological University, 2020)
Dementia is an illness that leads to several disabilities due to the decline of the brain. It can affect people of all ages especially those above 60 years old. According to a study done by the institute of Mental Health in 2015, it is calculated that 1 in 10 people aged 60 and above may have dementia. To date, there is no known cure for dementia. Researchers have found ways that the patients with dementia can follow to cope with their forgetfulness such as reminding them of reality, keeping a regular routine and using memory aids. As it is hard for dementia patients’ guardians or caretakers to help them due to their inexperience and knowledge of dementia, person-centred care is introduced. Person-centred care is practised to understand a person’s uniqueness, retention of the need for self-recognition and identity and their ability to act and respond to the environment around them. It involves the patient and caregiver to share their knowledge, learn about the patient and come up with an ideal care plan to help in recovery. Despite this, person-centred care for dementia faces a challenge. It lacks existing technology resources in order to help assist the care centre operations. The PEAR System is developed to be used by the professional in the care centre to provide a better care for dementia patients. The application will follow the principles of person-centred care by gathering every dementia patients’ information and store it on a server. It will recommend suitable care plans based on the given information and store patients’ progress keyed in by the caregivers from their observation. The key objective is to improve the PEAR back-end system which consists of the web application using ASP.NET MVC5 Architecture, Application Programming Interface, Firebase, APC Web Hosting and Microsoft SQL Database Server. This includes implementing generalising API to lessen API calls and improve web application. Testing will be conducted to evaluate the system compliances and fix errors that may degrade the user experience.